2012
DOI: 10.1128/jcm.00273-12
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneously High Prevalences of Hepatitis B and C Virus Infections in a Population in Putian County, China

Abstract: cThis study investigated a rare area of endemicity with a high prevalence of both hepatitis B virus (HBV) and hepatitis C virus (HCV) infections, in Putian County, China. Among 1,050 subjects, the overall prevalence of HBsAg seropositivity was 15.8%, and that of anti-HCV seropositivity was 28.9%. Intrafamilial viral transmission might be the major cause of the high prevalence of HBV infection in this region. However, HCV infection was shown to be associated with the use of inadequately sterilized medical equip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…In fact, more than half of residents over the age of 40 years were infected with HCV. The study authors [8] noted that this finding was unexpected and may have been due to the lack of sterilization of medical equipment that was common practice in this region until the 1990s [8] (Table 1).…”
Section: Epidemiology Reviewmentioning
confidence: 87%
See 1 more Smart Citation
“…In fact, more than half of residents over the age of 40 years were infected with HCV. The study authors [8] noted that this finding was unexpected and may have been due to the lack of sterilization of medical equipment that was common practice in this region until the 1990s [8] (Table 1).…”
Section: Epidemiology Reviewmentioning
confidence: 87%
“…In Putian County [8], HCV prevalence was found to increase significantly (p = 0.0001) with age, ranging from 12 % in those 20-29 years of age to 69 % in those aged 60-69 years [8]. In fact, more than half of residents over the age of 40 years were infected with HCV.…”
Section: Epidemiology Reviewmentioning
confidence: 88%
“…In the same year, 10.4% of 14,997 cases screened positive for HBV in insular regions of southeast China [9]. Prior to this, an examination of 1050 people in Putian found that 15.8% tested positive for HBV [10]. Military personnel experience greater exposure to transmissible infectious diseases due to the nature of their missions [11, 12].…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate reprocessing of medical devices has been considered as one of the factors contributing to higher rates of HAIs in developing countries [2,3,17]. An acute hepatitis outbreak in Gujarat in India and a high prevalence of anti-hepatitis C seropositivity (28.9%) in a Chinese village were both attributed to inadequately sterilized medical equipment, including needles and syringes [18,19].…”
Section: Introductionmentioning
confidence: 99%